A History of Human and Civil Rights in the Somerville Latino Community, 2004 - Nicholson, Lindsey; Van Nieuwenhuizen, Adrienne (Tufts Archival Research Center, 2006)
Final project report by Lindsey Nicholson and Adrienne Van Nieuwenhuizen.